Early life inflammation — it sticks to the brain. (August 2019) - Pittman, Quentin J; Gómez, Carlos D; Read, Justin; Lewis, Megan L; Acharjee, Shaona
Highlights: Neonatal inflammation causes long-term changes in rodent behavior. Neonatal inflammation also alters susceptibility to disease models. Changes in the endocannabinoid system are causal for some behavioral changes. Severe childhood infection may increase risk of later life psychiatric problems. Abstract : Sickness is common in human babies, but relatively rare in lab rodents. When specified pathogen-free mice or rats are exposed to systemic inflammation within an early life time window, there are long-term changes in the brain and behavior that persist into adulthood. Molecules such as TNFα and IL-1β that are transiently expressed in the brain after an early life inflammatory episode interact with the changing neuronal and glial environment during early life to cause long-lasting changes in a variety of signalling molecules, receptors and cell numbers that persist into adulthood. Among these, endocannabinoid system alterations are causal for some behavioral changes, but further studies focusing on other potential mechanisms are needed. Finally, a number of animal models of disease are altered by early life inflammation; similar studies in human populations are beginning to appear that indicate a correlation with severe, but not with more benign early life infections and neuropsychiatric problems later in life.